Creating and curating a community of practice: introducing the evidence synthesis Hackathon and a special series in evidence synthesis technology - Haddaway, Neal R.; Westgate, Martin J. (Environmental evidence, 2020)
Evidence synthesis is a vital part of evidence-informed decision-making, but high growth in the volume of research evidence over recent decades has made efficient evidence synthesis increasingly challenging. As the appreciation and need for timely and rigorous evidence synthesis continue to grow, so too will the need for tools and frameworks to conduct reviews of expanding evidence bases in an efficient and time-sensitive manner. Efforts to future-proof evidence synthesis through the development of new evidence synthesis technology (ESTech) have so far been isolated across interested individuals or groups, with no concerted effort to collaborate or build communities of practice in technology production. We established the evidence synthesis Hackathon to stimulate collaboration and the production of Free and Open Source Software and frameworks to support evidence synthesis. Here, we introduce a special series of papers on ESTech, and invite the readers of environmental evidence to submit manuscripts introducing and validating novel tools and frameworks. We hope this collection will help to consolidate ESTech development efforts and we encourage readers to join the ESTech revolution. In order to future-proof evidence synthesis against the evidence avalanche, we must support community enthusiasm for ESTech, reduce redundancy in tool design, collaborate and share capacity in tool production, and reduce inequalities in software accessibility.